Training tuberculosis laboratory workers in LED-fluorescence microscopy: experience learned in Argentina (2018)
Objective To assess a LED-fluorescence microscopy (LED-FM) capacitation program for the training of laboratory technicians without previous experience in FM.Methods We evaluated a teaching program that consists of a three-day course followed by an “in situ” two-month phase in which technicians acquired skills without the help of a FM expert; in order to gain confidence to recognize auramine-stained bacillus, during this phase, technicians examined duplicate slides stained by Ziehl Neelsen (ZN) and FM in a unblinded way. Technicians with acceptable performance, continued with a blinded-training period. Testing panels and rechecking process were used to evaluate proficiency after different length of experience.Results Post-course panel results showed that 70% of trainees made Low False Positive errors (LFPs). Analysis of two other panels showed that LFPs significantly decreased (Chi-squared test, p0.05) as the “in situ” training phase progressed. Processing at least three slides/day was associated with acceptable performance. During the blinded-training period, results of the rechecking process showed that sensitivity (96.8%) and specificity (99.8%) levels were satisfactory.Conclusion Moderate training (a three-day course) is not enough to make technicians proficient in LED-FM; however,great ability can be reached after a short “in situ” training phase even without the presence of experienced staff available in field to review doubtful results. Training was more effective in services with a minimum workload of 750 slides/year.